2018
DOI: 10.5530/pj.2018.3.66
|View full text |Cite
|
Sign up to set email alerts
|

Nephroprotective Effect of Aqueous Extract of Pimpinella anisum in Gentamicin Induced Nephrotoxicity in Wistar Rats

Abstract: Background: Pimpinella anisum known for its various medicinal properties is also a natural antioxidant and a free radical scavenger with no documented evidence as a nephroprotective agent. Objective: To evaluate the nephroprotective activity of aqueous extract of Pimpinella anisum seeds in a rodent model of gentamicin induced nephrotoxicity. Materials and Methods: Wistar albino rats of either sex, weighing 150-200 g was divided into 5 groups; normal saline, gentamicin 80mg/kg, intraperitoneally for 8 days, aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 18 publications
4
15
0
Order By: Relevance
“…In our study, gentamicin caused kidney dysfunction, this marked by increased levels of creatinine, urea, and this similar with previous studies. 16,19,2,20,21 In this study, administration of Sterculia rubiginosa leaf extract significantly reduced creatinine, urea and kidney tissue damage levels. The antioxidant activity of Sterculia rubiginosa leaf extract was carried out in vitro by the FRAP and DPPH methods.…”
Section: The Distance Between Glomerulus and Bowman Capsulesmentioning
confidence: 60%
“…In our study, gentamicin caused kidney dysfunction, this marked by increased levels of creatinine, urea, and this similar with previous studies. 16,19,2,20,21 In this study, administration of Sterculia rubiginosa leaf extract significantly reduced creatinine, urea and kidney tissue damage levels. The antioxidant activity of Sterculia rubiginosa leaf extract was carried out in vitro by the FRAP and DPPH methods.…”
Section: The Distance Between Glomerulus and Bowman Capsulesmentioning
confidence: 60%
“…Drug-induced nephrotoxicity is the main precursor for kidney diseases, including acute renal failure and chronic renal failure (Aiswarya et al, 2018). Immunosuppressive agents suppress the immune system in order to avoid graft rejections after organ transplantation.These agents, especially tacrolimus and cyclosporine, are associated with the high risk of toxicities, including renal toxicity, neurotoxicity, etc.…”
Section: Histopathological Studiesmentioning
confidence: 99%
“…The traditional system of medicine like Unani and Siddha showed that the plant Cubeba of icinalis is effective in treating various genitor urinary tract infections and in gravel and stones from kidney and bladder. It is also known to show positive effects in kidney disorders and hence is the plant of choice in the current study (Aiswarya et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This rate was 7 times as high as the rate for those aged 55-64 (26 per 10,000). [13] In India, GBD 2015 ranks nephrotoxicity as the eighth leading cause of death. Deaths due to renal toxicity constituted 2.9% of all deaths in 2010-2013 among 15-69 years old, an increase of 50% from 2001-2003.…”
Section: Statisticsmentioning
confidence: 99%